Methyl-4-phenylpyridinium (MPP+) differentially affects monoamine release and re-uptake in murine embryonic stem cell-derived dopaminergic and serotonergic neurons - Martí, Yasmina Gil; Lau, Thorsten; Schloss, Patrick (Molecular and cellular neuroscience, 2017)
1-Methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP) is known to selectively damage dopaminergic (DA) cells in the substantia nigra and to produce symptoms which are alike to those observed in Parkinson's disease (PD). Based on the similarity between MPTP-induced neurotoxicity and PD-related neuropathology, application of MPTP or its metabolite methyl-4-phenylpyridinium (MPP+) was successfully established in experimental rodent models to study PD-related neurodegenerative events. MPP+ is taken up by the dopamine transporter (DAT) into DA neurons where it exerts its neurotoxic action on mitochondria by affecting complex I of the respiratory chain. MPP+ is also a high affinity substrate for the serotonin transporter (SERT), however little is known about possible toxic effects of MPP+ on serotonergic (5-HT) neurons. In order to compare cell type-specific effects of MPP+ treatment, we have differentiated mouse embryonic stem (ES) cells into DA and 5-HT neurons and studied the impact of MPP+ treatment on both types of monoaminergic neurons in vitro. MPP+ treatment impacts on mitochondrial membrane potential in DA as well as 5-HT ES cell-derived neurons. Although mitochondria metabolisms are similarly affected, synaptic vesicle cycling is only impaired in DA ES cell-derived neurons. Most importantly we show that MPP+ induces DAT externalization in DA neurons, but internalization of SERT in 5-HT neurons. This diverse MPP+-induced transporter trafficking is reflected by elevated substrate uptake in DA neurons, and diminished substrate uptake in 5-HT neurons. In summary, our experimental data point toward differential effects of MPP+ intoxication on neurotransmitter release and re-uptake in different types of monoaminergic neurons.